The anticancer effects of Metformin in the male germ tumor SEM-1 cell line are mediated by HMGA1 - Salatino, Alessandro; Mirabelli, Maria; Chiefari, Eusebio; Greco, Marta; Di Vito, Anna; Bonapace, Giuseppe; Brunetti, Francesco S.; Crocerossa, Fabio; Epstein, Alan L.; Foti, Daniela P.; Brunetti, Antonio (Frontiers in Endocrinology, 2022)
Introduction: Germ cell tumors (GCTs) are the most common cancers in young men. In most cases, these tumors arise from the testis and rarely develop from extragonadal sites probably due to primordial germ cells (PGCs) migration errors. Male GCTs usually respond well to cisplatin-based chemotherapy, but the risk of toxicity for affected patients is high and new therapeutic strategies are needed. Although there has been widespread interest in Metformin (Met) as an anticancer agent over the past decades, evidence supporting its use in male GCTs is limited, and its cellular and molecular mode of action is still unclear. Methods: SEM-1 cells, a newly established human cell line of extragonadal origin, were treated with Met. Cell viability was studied by MTT assay and cell migration by wound healing assay. The effect of Met on 3D spheroid formation was determined by seeding SEM-1 cells in appropriate cell suspension culture conditions, and cell cycle was characterized by flow cytometry. Factors involved in PGCs migration and GCT invasion, such as IGFBP1, IGF1R, MMP-11 and c-Kit, together with cyclin D1 (a key regulator of cell cycle progression), and the upstream factor, HMGA1, were determined by immunoblots. Results: Treatment of SEM-1 cells with Met resulted in a potent and dose-dependent reduction of cell proliferation, as demonstrated by decreased nuclear abundance of cyclin D1, and block of cell cycle in the G1 phase. Also, Met prevented the formation of 3D spheroids, and blocked cell migration in wound healing assays by reducing the expression of IGFBP1, IGF1R and MMP-11. Both, IGFBP1 and MMP-11 are under control of HMGA1, a chromatin-associated protein involved in the modulation of important oncogenic, metabolic and embryological processes. Intriguingly, an early reduction in the nuclear abundance of HMGA1 occurred in SEM-1 cells treated with Met. Conclusions: Our results document the antiproliferative and antimigratory effects of Met in SEM-1 cells, a novel model for the study of male GCTs. The anticancer properties of Met in SEM-1 cells appeared to be related to its ability to interfere with HMGA1 and downstream targets, including cyclin D1, the IGFs system, and MMP-11.